The common sense of differentiation meeting spesific learner needs in the regular classroom - Kiernan, Leslie J.; Frost, Frank; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2005)
The three video presentations take viewers into a variety of classrooms at different grade areas and across different subject areas to observe how teachers uncover learner needs, plan instruction to meet those needs, and develop classroom routines that allow attention to a range of learner needs. Workshops in the facilitator's guide provide opportunities for additional exploration, application, and sharing related to some of the key principles and practices of effective differentiation for diverse learners
tape 1. Discovering learner needs (37 min.) -- tape 2. Techniques for adjusting instruction (46 min.) -- tape 3. Classroom routines (35 min.)
Title from title screen
Copy available in DVD format
Editor, Judith E. Herbert ; camera, Richard Diamond, Dominic Desantis ; sound, Rick Patterson, Jonathan Cohen, William Kaplan
Consultant: Carol Ann Tomlinson
Keywords: Individualized instruction; Mixed ability grouping in education; Curriculum planning